Controlling chromaticity by lamellar gratings - Ichikawa Hiroyuki; Arita Naoki; Shikimi Keigo; Maeda Kei; Tani Ryunosuke (EPJ Web of Conferences, 2022)
Fundamental numerical study on controlling chromaticity with the simplest diffractive structure is carried out. Observed various characteristics on transmission/reflection and dielectric/metal will be useful guidelines for practical optimisation of device structures.